Design of Active Frequency Selective Surface with Curved Composite Structures and Tunable Frequency Response - In-Gon Lee; Yong Bae Park; Heung-Jae Chun; Yoon-Jae Kim; Ic-Pyo Hong (International Journal of Antennas and Propagation)
We present an active frequency selective surface (AFSS) consisting of a curved composite structure that provides structural stability and robustness. The proposed structure can operate on either the C-band (OFF state) or X-band (ON state) by controlling the PIN diode located between the cross-shaped loop and the inductive stub on the surface. Moreover, it minimizes parasitic couplings through grid-type on/off bias circuits and via holes. Thus, the AFSS guarantees isolation from the unit cell, which is a downside of a previous control technique called reconfigurable frequency selective surface. We analyzed the impact of composite structures and the three-dimensional shape on the AFSS transmission with a foam-core sandwich structure, which is light and mechanically strong, by considering conditions of a real application environment.